Demokrasi dan Kekuasaan Adat: Potensi Eksklusi Akses Dana Desa bagi Eks Pengungsi Timor-Leste - Ali Maksum; Wida Ayu Puspitosari; Juwita Hayyuning Prastiwi (Society, 2020)
This research aims to reveal the relations between democracy and customary power in handling the East Timorese ex-refugees in Belu Regency, East Nusa Tenggara Province, Indonesia, related to democratic practices More specifically, democracy is limited to the context of potential exclusion access of the Village Fund for new residents. This research used a qualitative and case studies approach to reveal democratic practices related to the implementation of Village Funds that are intertwined with the local culture. The subjects in this research were new residents in Fatuba’a Village which is geographically close to the cross-border between Indonesia and East Timor. Nearly half of Fatuba’a’s populations are new residents who are East Timorese ex-refugees. A large number of new residents have become a complex social problem for Fatuba’a Village. The data collection techniques consist of observation, in-depth interviews, and focus group discussions. The results showed that customary institutions play a significant role in distributing power both in aspects of government and village development, including the distribution of village funds-use. The Liudasik tribe is a successful dominant tribe obtaining legitimacy of the new residents by granting customary land as a place to live and farming for their contribution to elect the village head from the Liudasik tribe. In the context of the Village Fund, its use also shows the interdependence between new residents and the Liudasik tribe. Consequently, the new residents have an access to village funds. There is no exclusion of new residents for the Fatuba’a’s Village Fund-use. The dependence of new residents on customary institutions has perpetuated the customary power of the Liudasik tribe.